Prevention of Early Marriage in Religious and Health Perspectives in Petangguhan Village - Winda Junarda; Vivi Chairani; Novi Lestari; Siti Khadijah Azzahra; Andika Rifandi; Sholihatul Hamidah Daulay (Jurma : Jurnal Program Mahasiswa Kreatif, 2023)
The purpose of this study was to find out young people who married at an early age in the village of Petangguhan, and so that in the future there would be no more cases of early marriage in the village of Petaguhan. From a reproductive health point of view, adolescents who marry early will have a greater impact on reproductive health and even psychologically. The method used in this research is a type of qualitative research. The approach in this study uses a sociological approach that is related to one community with another. Primary data sources were obtained directly from the results of research interviews conducted with the health agency in the village of Petangguhan. Data on the dispensation rate for marriage were obtained from the Religious Courts, and some data from the village office, namely the village head who is also the secretary of the village of Petangguhan, Kab. Poor. The results of this study indicate that there are several impacts of early marriage, namely the causes of high maternal and infant mortality, low birth weight, birth injuries, and birth complications that occur in adolescents. prevention of early marriage, they want to carry out a youth posyandu in the village of Petaguhan.